2019
DOI: 10.3390/su11154050
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Method of Corn Stalk Fiber Material and Its Performance Investigation in Asphalt Concrete

Abstract: In this study, a bioresource material, corn stalks, were converted by a combination of physical and chemical methods into a corn stalk fiber material that can be utilized in an asphalt pavement. Firstly, corn stalk fiber was produced with different comminution times, mass fractions of sodium hydroxide solution, reaction times, and reaction temperatures. An orthogonal experimental method was employed to determine the optimal production process. The results show that the optimal comminution time was 3.5 min, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In recent years, the extraction of natural fibers from corn stalks and their applications in the construction industry, composite material industry and other fields have been carried out. Boufi et al produced cellulose nanofibers from cornstalk by a conventional high-speed blender [4], Chen et al carried out a study on the performance investigation of cornstalk fibrous materials in asphalt concrete [5], and Vo et al explored the correlation between genotype biochemical characteristics and mechanical properties of cornstalk-polyethylene composites [6]. However, these studies have carried out research on the properties of cornstalks fiber from a macroscopic perspective, and the research on the microscopic scale i elatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the extraction of natural fibers from corn stalks and their applications in the construction industry, composite material industry and other fields have been carried out. Boufi et al produced cellulose nanofibers from cornstalk by a conventional high-speed blender [4], Chen et al carried out a study on the performance investigation of cornstalk fibrous materials in asphalt concrete [5], and Vo et al explored the correlation between genotype biochemical characteristics and mechanical properties of cornstalk-polyethylene composites [6]. However, these studies have carried out research on the properties of cornstalks fiber from a macroscopic perspective, and the research on the microscopic scale i elatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Although plenty of studies have demonstrated the feasibility of utilizing lignin as a bitumen modifier, the application of the Kraft lignin (KL) and the corn stalk lignin (CL) as bitumen modifier are quite limited. Both KL (25 million tons/year) and CL (250 million tons/year) have abundant source from paper producing industries and agricultural productions [ 20 , 24 ], respectively. To date, the performance of lignin modified bituminous binder and mixture have still not been comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As more attention has been drawn on sustainable development, concern of the environmental problem induced by the abundant discarded corn stalks (CS) produced from agricultural industry is growing rapidly, which is more severe in China because of its high annual output of corn stalks (about 250 million tons per year) and poor efficiency of waste utilization [ 1 ]. Traditional treatment of corn stalks is combusting them directly as a kind of fuel, whose energy efficiency is low and consequently causes large amounts of CO, CO 2 and NO 2 emissions leading to increase in diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, utilizing hydrochar as binder modifiers instead of solid fuel seems more reasonable. As proof, Chen et al made worthful achievement by exploring an innovative way of converting corn stalks to fiber material [ 1 ] and performance evaluation of asphalt modified by corn stalk fiber [ 21 ]. What is more, Bao et al investigated the chemical composition and rheological properties of bio-asphalt, the residue from corn waste processed through acidification and polymerization [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation